RANCANG BANGUN APLIKASI KRIPTOGRAFI PENGAMANAN TRANSMISI DATA MULTIMEDIA MENGGUNAKAN ALGORITMA DATA ENCRYPTION STANDARD (DES) - Nita Syahputri (Majalah Ilmiah METHODA, 2019)
With the development in the field of information technology, data communication technology and multimedia technology at the moment that is so rapid, the most important thing to think about is the security problem because it will guarantee data, especially multimedia data, so that it is not stolen by unauthorized people. To overcome this, the security technique used is the DES (Data Encryption Standard) algorithm which serves to provide security of multimedia data transmission by encrypting multimedia data so that unauthorized people will not be able to read the multimedia data without having the key, this technique is very effective because it can maintain the confidentiality of data, especially multimedia data and also requires a very long time to be able to find the right key.